BUSINESS MARKETING MANAGEMENT OF J.Co MEDAN COMPANY - Purba, Ririn Yovangka; Nst, Asrindah; Amin, Afriadi (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2024)
This study aims to analyze the impact of business level strategy on J.CO company that conducts corporate activities to achieve competitive advantage in the market. J.CO is a local company that offers different donut flavors and several types of coffee. The donuts served by J.CO are very soft and fresh, and the various fruit toppings and fillings make their appearance even more appetizing. J.CO was founded on July 26, 2005 in Jakarta. Business level strategy is a decision taken by a company to gain competitive advantage in a particular market. usually done by managers to achieve success when competing with companies that offer similar products.